2015
DOI: 10.1016/j.jpainsymman.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Re: Long-Term Psychosocial Outcomes Among Bereaved Siblings of Children With Cancer

Abstract: there is scant work in the area of hematological oncology. As a result, there is an obvious need to call for development, adoption, and investigation of collaborative care models linking PC and hematology. Hopefully, this letter can be a catalyst for debate that will foster a new direction in clinical service and research at the interface of PC and hematology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There is a period of vulnerability for the siblings during and after the sick child’s death; supporting activities seem to be of importance (Jenholt Nolbris et al, 2014; Rosenberg et al, 2015). Siblings may even experience negative consequences of the child’s loss many years later (Jenholt Nolbris et al, 2014; van der Geest, Darlington, & van den Heuvel-Eibrink, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is a period of vulnerability for the siblings during and after the sick child’s death; supporting activities seem to be of importance (Jenholt Nolbris et al, 2014; Rosenberg et al, 2015). Siblings may even experience negative consequences of the child’s loss many years later (Jenholt Nolbris et al, 2014; van der Geest, Darlington, & van den Heuvel-Eibrink, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…18 Attention after the child's death is often focused at parents (the main caregivers for their child); consequently, siblings can feel abandoned. In a previous study on the wellbeing of bereaved siblings of children with cancer we showed that the death of a child may have negative consequences for bereaved siblings, even after many years.…”
Section: Adequate Bereavement Carementioning
confidence: 99%
“…In a previous study on the wellbeing of bereaved siblings of children with cancer we showed that the death of a child may have negative consequences for bereaved siblings, even after many years. 18 Support for siblings should be better organised. 18 GPs play an important role in follow-up of parents and siblings, and, if necessary, in referring them to other healthcare professionals.…”
Section: Adequate Bereavement Carementioning
confidence: 99%
See 1 more Smart Citation
“…The emotional problems experienced by cancer-bereaved siblings (e.g., loneliness, anxiety, and anger) seem to start during the dying child’s illness [ 6 ]. There are very few studies exploring the long-term adjustment of bereaved siblings [ 10 ]. One study observed unresolved grief in the majority (54%) of young adults 2–9 years after losing a sibling to cancer, and only 11% reported having worked through their grief completely [ 11 ].…”
Section: Introductionmentioning
confidence: 99%